Chronic stress, depression and personality type in patients with myasthenia gravis. (5th September 2019) - Bogdan, A.; Barnett, C.; Ali, A.; AlQwaifly, M.; Abraham, A.; Mannan, S.; Ng, E.; Bril, V.
Abstract : Background and purpose: Stress is a known risk factor for the onset and modulation of disease activity in autoimmune disorders. The aim of this cross‐sectional study was to determine any associations between myasthenia gravis (MG) severity and chronic stress, depression and personality type. Methods: In all, 179 consecutive adult patients with confirmed MG attending the Neuromuscular Clinic between March 2017 and December 2017 were included. At baseline, patients were assessed clinically and they completed self‐administered scales for disease severity, perceived stress, depression and personality type. Results: Higher disease severity [Myasthenia Gravis Impairment Index (MGII)] showed a moderate correlation with depression score (Beck's Depression Inventory, Second Edition, r = 0.52, P < 0.001) and a lower correlation with chronic stress (Trier Inventory for Assessment of Chronic Stress, r = 0.28, P = 0.001). Chronic stress scores were different according to personality types (anova, P = 0.02). The linear regression model with MGII score as the dependent variable showed R 2 = 0.34, likelihood ratio chi‐squared 74.55, with P < 0.0001. The only variables that predicted disease severity were depression scores ( P < 0.0001) and female sex ( P = 0.003). Conclusions: A significant association of MG severity with depression and chronic stress was found, as well as with female gender. These findings should raise awareness that the long‐term management of MG should address depression and potential stress and consider behavioural management to prevent stress‐related immune imbalance.